2016
DOI: 10.1073/pnas.1606012113
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of an HP1-like protein is a prerequisite for heterochromatin body formation in Tetrahymena DNA elimination

Abstract: Multiple heterochromatic loci are often clustered into a higher order nuclear architecture called a heterochromatin body in diverse eukaryotes. Although phosphorylation of Heterochromatin Protein 1 (HP1) family proteins regulates heterochromatin dynamics, its role in heterochromatin bodies remains unknown. We previously reported that dephosphorylation of the HP1-like protein Pdd1p is required for the formation of heterochromatin bodies during the process of programmed DNA elimination in the ciliated protozoan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
(64 reference statements)
1
10
0
Order By: Relevance
“…These results indicate that the Pdd1p-containing bodies that form in the absence of Jub6p are still associated with heterochromatin and, thus, probably represent an abnormal type of heterochromatin body caused by disturbance of the subnuclear localization of heterochromatin within the new MAC. This abnormal heterochromatin body formation is unlikely to be due to blockage of DNA elimination, as such abnormal heterochromatin bodies have not been detected in our previous studies of other DNA-elimination-defective mutants by the same immunofluorescent staining procedures (Kataoka and Mochizuki, 2015;Kataoka et al, 2016;Vogt and Mochizuki, 2013).…”
Section: Jub6p Is Essential For the Formation Of Heterochromatin Bodiessupporting
confidence: 44%
See 1 more Smart Citation
“…These results indicate that the Pdd1p-containing bodies that form in the absence of Jub6p are still associated with heterochromatin and, thus, probably represent an abnormal type of heterochromatin body caused by disturbance of the subnuclear localization of heterochromatin within the new MAC. This abnormal heterochromatin body formation is unlikely to be due to blockage of DNA elimination, as such abnormal heterochromatin bodies have not been detected in our previous studies of other DNA-elimination-defective mutants by the same immunofluorescent staining procedures (Kataoka and Mochizuki, 2015;Kataoka et al, 2016;Vogt and Mochizuki, 2013).…”
Section: Jub6p Is Essential For the Formation Of Heterochromatin Bodiessupporting
confidence: 44%
“…Our previous study suggests that heterochromatin body assembly during new MAC development requires the phosphorylation (Kataoka et al, 2016) and subsequent dephosphorylation (Kataoka and Mochizuki, 2015) of Pdd1p. Pdd1p is phosphorylated at multiple serine and threonine residues, and phosphorylated Pdd1p migrates more slowly than unphosphorylated Pdd1p in standard SDS-PAGE Fig.…”
Section: Jub6p Is Not Required For the Phosphorylationdephosphorylatimentioning
confidence: 97%
“…We examined whether TPB1-dependent IESs form heterochromatin like other IESs, recruiting proteins such as Pdd1p . Upon analyzing H3K9me3, H3K27me3, and Pdd1p occupancy using published ChIP-seq (chromatin immunoprecipitation [ChIP] combined with high-throughput sequencing) data Kataoka et al 2016), we found much lower occupancy of all three proteins in TPB1-dependent IESs than other IESs (Fig. 4B).…”
Section: Failure To Excise the Dop1 Ies Results In Large Vacuolesmentioning
confidence: 98%
“…We reanalyzed published ChIP-seq data for Pdd1p , H3K9me3, and H3K27me3 (Kataoka et al 2016). First, we created an improved genome-wide IES data set because we noticed that a published data set (Noto et al 2015) was missing a number of IESs (especially those bounded by micronuclear assembly gaps).…”
Section: Pdd1p H3k9me3 and H3k27me3 Occupancymentioning
confidence: 99%
“…Filtered Twi1 RNPs escape the parental macronucleus and relocalize, along with Twi11 RNPs, to developing zygotic macronuclei, where an amplification of IES-targeting scnRNA occurs (Mochizuki et al 2002;Noto et al 2015). Ultimately, scnRNA RNPs trigger the trimethylation of histone 3 lysine 9 (H3K9me3) and lysine 27, which recruit chromodomain proteins including Pdd1p that coalesce heterochromatin into punctate foci thought to support IES elimination (Kataoka et al 2016). H3K9me3 is unique to the developing macronuclei of Tetrahymena; remarkably, differentiated macronuclei lack H3K9me3 heterochromatin (Taverna et al 2002).…”
Section: Introductionmentioning
confidence: 99%